2022
DOI: 10.1371/journal.pone.0261627
|View full text |Cite
|
Sign up to set email alerts
|

Silver diamine fluoride and oral health-related quality of life: A review and network meta-analysis

Abstract: Objective Silver diamine fluoride (SDF) is an effective non-surgical treatment for dental caries which may also impact oral health-related quality of life (OHRQoL). The objective of this study was to conduct a network meta-analysis of SDF versus other standard of care therapies on OHRQoL. Data sources Studies published in PubMed/MEDLINE, Scopus, or Web of Science through July 2021 with no date or language restrictions. Study selection Any randomized controlled trial, cohort, or case-control study that incl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…19 A network meta-analysis found no differences in oral health-related quality of life (OHRQoL) between SDF and other non-surgical treatments for dental caries in children. 20 Duangthip 21 also found that using SDF for caries arrest in preschool children is safe, with no signi cant adverse effects reported by parents.…”
Section: Discussionmentioning
confidence: 97%
“…19 A network meta-analysis found no differences in oral health-related quality of life (OHRQoL) between SDF and other non-surgical treatments for dental caries in children. 20 Duangthip 21 also found that using SDF for caries arrest in preschool children is safe, with no signi cant adverse effects reported by parents.…”
Section: Discussionmentioning
confidence: 97%
“…Ruff et al conducted a meta-analysis comparing the influence of SDF on the OHRQoL versus other standard therapy methods [ 19 ]. The findings showed that the improvement in OHRQoL after treatment with SDF did not differ from results with other treatment options such as atraumatic restorations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently conducted meta-analysis comparing the influence of SDF on the OHRQoL with other therapy methods, it was noted that there was a very limited number of studies that considered the effect of SDF on the OHRqoL [ 19 ]. Although it was found that the OHRQoL was not notably affected by SDF when compared to other treatment options, this conclusion was constrained by the small number of studies in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the unfavorable view, parents agree with SDF application if they perceive their child as uncooperative and compare it with other options such as ART or general sedation (Crystal et al, 2017). Oral quality of life after SDF application is still under investigation (Ruff et al, 2022). A recent study concluded that it is not noticeably affected by SDF application, but further studies are needed for the impact of the baseline severity of caries treated by SDF and the application of SDF on posterior versus anterior teeth on the oral health-related quality of life (OHRQoL) (Ruff et al, 2022).…”
Section: Case Reportmentioning
confidence: 99%
“…Oral quality of life after SDF application is still under investigation (Ruff et al, 2022). A recent study concluded that it is not noticeably affected by SDF application, but further studies are needed for the impact of the baseline severity of caries treated by SDF and the application of SDF on posterior versus anterior teeth on the oral health-related quality of life (OHRQoL) (Ruff et al, 2022).…”
Section: Case Reportmentioning
confidence: 99%